Chlorine salt corrosive liquid, iron negative electrode and preparation method of iron negative electrode

By using chloride corrosion liquid to corrode and annealing the foam iron, an iron negative electrode with high area specific capacity, rate performance and cycle stability was prepared, which solved the problem of volume change and low conductivity of existing iron negative electrode materials during circulation.

CN119571327APending Publication Date: 2025-03-07XINYANG NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411633740.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing iron anode materials change in volume and low conductivity during the cycle process, resulting in poor stability and poor dynamics of the electrode structure, showing low cycle stability and rate performance.

Method used

The iron foam is corroded by chlorine corrosion liquid to form a uniform micro-nano structure, and annealed under the protection of inert gas to prepare an iron negative electrode composed of a foam iron framework and iron tetroxide particles.

Benefits of technology

The specific area capacity, rate performance and cycle stability of the iron negative electrode are improved. The specific capacity can reach more than 1.33mAh cm-2 at the current density of 4mA cm-2, and the specific capacity is more than 0.81mAh cm-2 at the current density of 32mA cm-2, and the stable cycle is more than 300 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571327A_ABST
    Figure CN119571327A_ABST
Patent Text Reader

Abstract

The invention relates to chlorine salt corrosive liquid, an iron negative electrode and a preparation method of the iron negative electrode, and belongs to the technical field of electrochemical energy storage device electrode materials. Firstly, foam iron is placed in acetone and ethyl alcohol for ultrasonic cleaning to remove dirt and oil films on the surface, then the foam iron is soaked in chlorine salt corrosion liquid for corrosion, a large number of sheet structures are generated on the surface of the treated foam iron, then the foam iron is simply cleaned with deionized water, annealing treatment is conducted after drying, and the foam iron is obtained. Micron-sized particles are generated on the surface of the annealed foam iron. The integrated electrode constructed without an additional iron source has good conductivity, the specific surface area of the material can be increased by combining the three-dimensional skeleton structure of the foam iron and the micron-sized ferroferric oxide particles, the change of the electrode structure in the cycle process is slowed down, and the rate capability, the area specific capacity and the cycle stability of the electrode are improved. The preparation method is simple and low in cost, and has batch production potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode materials for electrochemical energy storage devices, and in particular to a chloride salt corrosive solution, an iron negative electrode and a preparation method thereof. Background Art

[0002] Nickel-iron batteries have abundant raw materials, low cost, high theoretical specific capacity, intrinsic safety, and require less maintenance during use. They are currently widely used in lighting systems in railways and mines.

[0003] The iron negative electrode material of nickel-iron batteries has problems such as volume change during the cycle and low conductivity of intermediate products, which will lead to poor electrode structural stability and poor electrode kinetics, showing low cycle stability and rate performance, affecting the performance of the entire battery. At present, commercial iron negative electrodes mainly use powdered iron-based materials. Conductive agents and polymer binders need to be added during the electrode production process. The addition of the two will affect the conductivity of the electrode, and when a higher surface density is required, the thickness of the electrode material needs to be increased, which further weakens the conductivity and ion conductivity of the electrode, resulting in worse rate characteristics and cycle stability of the electrode.

[0004] Iron foam has a unique porous structure and excellent physical and chemical properties, and has great application potential in iron negative electrodes. However, when iron foam is directly used as an iron negative electrode, it exhibits low area specific capacity and poor cycle stability due to its small specific surface area. Studies have found that Fe(OH) can be synthesized in situ on the surface of iron foam using an electrochemical activation strategy. 3 Thin films can improve the area specific capacity of foamed iron to a certain extent. However, this method has limited capacity improvement and cannot fully utilize the foamed iron phase, so its commercial prospects are low. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a chloride salt corrosion solution, an iron negative electrode and a preparation method thereof, so as to solve the problems of low area specific capacity, poor rate performance and cycle stability of the existing iron negative electrode.

[0006] In one aspect, the present invention provides a chloride salt etching solution comprising metal cations, hydrogen ions and chloride ions.

[0007] Furthermore, the concentration of the metal cations is 0.1-1M, the concentration of the hydrogen ions is 0.05-2M, and the concentration of the chloride ions is 0.05-3M.

[0008] Furthermore, the raw materials for preparing the chloride salt etching solution are dilute hydrochloric acid and chloride salt solution.

[0009] Furthermore, the chloride salt is one or more of sodium chloride, potassium chloride, ammonium chloride, calcium chloride and zinc chloride.

[0010] In another aspect, the present invention provides a method for preparing an iron negative electrode, comprising the following steps:

[0011] S1. Clean the foam iron with acetone and ethanol to remove dirt and surface oil film;

[0012] S2, soaking the cleaned foamed iron in a chloride salt corrosion solution for corrosion, then rinsing with deionized water, and then vacuum drying;

[0013] S3: annealing the dried foamed iron under the protection of an inert gas, and naturally cooling it to room temperature to obtain an iron negative electrode.

[0014] Furthermore, the pore density of the foamed iron is 50-130ppi.

[0015] Furthermore, in step S2, the vacuum drying temperature is 40-80°C, and the vacuum drying time is 6-12 hours.

[0016] Furthermore, in step S3, the annealing temperature is 600°C-1000°C, and the heating rate is 2-10°C min -1 , the heat preservation time is 2-6 hours.

[0017] In a third aspect, the present invention provides an iron negative electrode obtained by the preparation method of the present invention.

[0018] Furthermore, at 4 mA cm -2 The specific capacity is 1.33 mAh cm at a current density of -2 Above 32 mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 Above, stable cycle more than 300 times.

[0019] Fourthly, the iron negative electrode can be used to prepare nickel-iron batteries.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0021] 1. The present invention provides a chloride salt etching solution, including metal cations, hydrogen ions and chloride ions, which is prepared by dilute hydrochloric acid and chloride salt solution, and then mixed in proportion to corrode the foamed iron. In the solution where the two chloride ions coexist, a uniform micro-nano structure can be constructed on the surface of the foamed iron without destroying the foamed iron skeleton. The micro-nano structure has a large size and can improve the performance of the foamed iron, such as good conductivity and rate capability;

[0022] 2. The present invention also provides a method for preparing an iron negative electrode, which uses foamed iron as a raw material and is prepared through cleaning, corrosion and annealing processes, which is completely different from existing methods for preparing iron negative electrodes, such as powder bonding and electrochemistry. The preparation method of the present invention is simple, the raw materials are readily available, and it is easy to mass produce;

[0023] 3. The iron negative electrode prepared by the present invention is composed of a foam iron skeleton and ferroferric oxide particles in situ constructed on the foam iron skeleton: the micron-sized ferroferric oxide particles have high activity and large specific surface area, which can bring higher area specific capacity; the in-situ combination of foam iron and ferroferric oxide active material can improve the overall conductivity of the electrode; the three-dimensional pore structure of the foam iron can provide a buffer space for the deformation of the active material and improve the structural stability of the electrode. The integrated iron negative electrode obtained as a whole shows a high area specific capacity, rate performance and cycle stability. At 4mA cm -2 The specific capacity can reach 1.33 mAh cm at a current density of -2 Above 32 mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 Above, stable cycle more than 300 times;

[0024] 4. The raw materials of foamed iron can be purchased directly. The whole preparation process uses fewer types of medicines and reagents, with low cost, simple production process and short cycle, which is suitable for mass industrial production.

[0025] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0027] Figure 1 This is a scanning electron microscope (SEM) image of the foamed iron before annealing prepared in step 2 of Example 1 of the present invention;

[0028] Figure 2 This is a scanning electron microscope (SEM) image of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0029] Figure 3 is an X-ray diffraction (XRD) pattern of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0030] Figure 4 1 is a cyclic voltammetry (CV) characteristic curve of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0031] Figure 5 The constant current charge-discharge (CP) curve of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0032] Figure 6 This is a cycle performance diagram of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0033] Figure 7 This is a SEM picture of the foamed iron before annealing prepared in step 2 of Example 2 of the present invention;

[0034] Figure 8 This is a SEM picture of the foamed iron before annealing prepared in step 2 of Example 3 of the present invention;

[0035] Fig. 9 This is a SEM picture of the foamed iron before annealing prepared in step 2 of Example 4 of the present invention;

[0036] Fig.10 This is a SEM picture of the foamed iron before annealing prepared in step 2 of Example 5 of the present invention;

[0037] Fig.11 This is a SEM picture of the foamed iron before annealing prepared in step 2 of Example 6 of the present invention;

[0038] Fig.12 This is a SEM picture of the foamed iron in Comparative Example 2 of the present invention;

[0039] Fig.13 The CV curve of the nickel-iron battery assembled with the iron negative electrode prepared in Example 1 of the present invention;

[0040] Fig.14 This is the CP curve of the nickel-iron battery assembled with the iron negative electrode prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0042] At present, the iron negative electrode of nickel-iron batteries is made by mixing the active material (iron, iron oxide or their mixture powder) and the conductive agent and binder in a certain proportion and coating them on the current collector. The preparation process is relatively complicated and the use of binders is not conducive to electron transmission. The deformation of the electrode material and the appearance of the passivation layer during the cycle will also cause the electrode performance to decay, resulting in poor electrode rate performance and cycle stability.

[0043] Iron foam has a unique porous structure and excellent physical and chemical properties, and has great application potential in iron negative electrodes. However, the surface of untreated iron foam is smooth, the specific surface area is small, and there are oxide layers and various impurities on the surface of iron foam, so the performance is poor when it is directly used as an iron negative electrode. The existing technology uses an electrochemical process to synthesize Fe(OH) 3 Thin film, the specific capacity of the obtained iron negative electrode is limited and the potential for mass production is poor.

[0044] The invention provides a chloride salt etching solution, which comprises metal cations, hydrogen ions and chloride ions.

[0045] The present invention provides a chloride salt etching solution, wherein the raw materials for preparing the solution include dilute hydrochloric acid and a chloride salt solution, which are mixed in proportion to corrode the foamed iron. Compared with the prior art, the micro-nano structure in situ generated on the surface of the foamed iron is more uniform, larger in size, and has higher performance when corroded in a solution where double chloride ions coexist.

[0046] Specifically, the concentration of the metal cations is 0.05-0.5M, the concentration of the hydrogen ions is 0.05-2M, and the concentration of the chloride ions is 0.05-3M.

[0047] In the present invention, the metal cation may be one or more of sodium ion, potassium ion, ammonium ion, calcium ion, and zinc ion.

[0048] Specifically, the raw materials for preparing the chloride salt etching solution are dilute hydrochloric acid and chloride salt solution.

[0049] Specifically, the chloride salt is one or more of sodium chloride, potassium chloride, ammonium chloride, calcium chloride and zinc chloride.

[0050] It should be noted that the metal cations, hydrogen ions and chloride ions in the corrosive solution play an important role in the entire corrosion process: hydrogen ions mainly react with the foamed iron to produce hydrogen; chloride ions will adhere to the surface of the foamed iron or penetrate into tiny gaps, accelerating the corrosion of the foamed iron while making the corrosion interface more uniform; in the presence of metal cations and chloride ions, the impurities in the foamed iron will react with the iron in a galvanic cell reaction, and the iron will lose electrons and be oxidized. This electrochemical process can effectively accelerate the corrosion process of the foamed iron; at the same time, by controlling the concentration of chloride ions in the reaction solution, the lamellar structure prepared by corrosion can be regulated.

[0051] The present invention also provides a method for preparing an iron negative electrode using the above chloride salt corrosion process, comprising the following steps:

[0052] S1. Clean the foam iron with acetone and ethanol to remove dirt and surface oil film;

[0053] S2, soaking the cleaned foam iron in a chloride salt corrosion solution, then washing it with deionized water, and finally vacuum drying it;

[0054] S3: annealing the dried foamed iron under the protection of an inert gas, and naturally cooling it to room temperature to obtain an iron negative electrode.

[0055] Compared with the prior art, the present invention provides a method for preparing an iron negative electrode, which uses foamed iron as a raw material and obtains the iron negative electrode through cleaning, corrosion and annealing processes. The iron negative electrode is composed of a foamed iron skeleton and ferrosoferric oxide particles constructed in situ on the foamed iron skeleton. The micron-sized ferrosoferric oxide particles have high activity and large specific surface area, which can bring higher area specific capacity. The in-situ combination of foamed iron and ferrosoferric oxide active substances can improve the overall conductivity of the electrode. The three-dimensional pore structure of foamed iron can provide a buffer space for the deformation of the active material and improve the structural stability of the electrode. The integrated iron negative electrode obtained as a whole exhibits high area specific capacity, rate performance and cycle stability at 4mA cm -2 The specific capacity is 1.33 mAh cm at a current density of -2 Above 32 mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 The above can be stably cycled for more than 300 times.

[0056] It should be noted that the foamed iron is firstly subjected to ultrasonic treatment in acetone and ethanol for 10-15 minutes. The purpose of the ultrasonic treatment is to remove dirt and oil film on the surface of the foamed iron.

[0057] Specifically, in step S2, the immersion corrosion time is 10-60 minutes.

[0058] It should be noted that during the immersion corrosion process, the sample was stirred on a magnetic stirrer in order to make the corrosion more uniform. The stirring speed was 60 r / min.

[0059] Specifically, in step S2, the vacuum drying temperature is 40-80°C, and the vacuum drying time is 6-12 hours.

[0060] It should be noted that the purpose of drying is to remove free water on the surface to prevent side reactions from occurring during the annealing process.

[0061] Specifically, the annealing temperature is 600°C-1000°C, and the heating rate is 2-10°C min -1 , the heat preservation time is 2-6 hours.

[0062] It should be noted that the reaction in step S2 is: hydrogen ions react with foamed iron to generate ferrous iron, ferrous iron further reacts with oxygen and water to generate ferric iron, and ferrous iron, ferric iron, water and oxygen react to generate iron hydroxide. Specifically, it can be represented by the following chemical formula:

[0063] Fe+2H + →Fe 2+ +H 2

[0064] 4Fe 2+ +O 2 +2H 2 O→4Fe 3+ +4OH -

[0065] Fe 2+ / Fe 3+ +H 2 O+O 2 →Fe 2+ Fe 3+ -LDH

[0066] The hydroxide obtained by the above reaction will be converted into an oxide at high temperature under an inert gas atmosphere.

[0067] Specifically, the pore density of the foamed iron is 50-130ppi.

[0068] Preferably, the pore density of the foamed iron is 95ppi.

[0069] It should be noted that the greater the pore density of the foamed iron, the more active interfaces per unit area there will be after immersion corrosion and annealing, and the higher the area specific capacity of the prepared iron negative electrode.

[0070] Specifically, the thickness of the foamed iron is 1-3 mm, and the iron content is ≥ 98%. Preferably, the thickness of the foamed iron is 1.5 mm.

[0071] It should be noted that the thicker the foamed iron is, the more iron it contains per unit area, and the higher the area specific capacity of the prepared iron negative electrode.

[0072] The iron negative electrode obtained by the preparation method provided by the present invention is composed of a foamed iron skeleton and ferroferric oxide particles attached to the foamed iron skeleton. Specifically, ferroferric oxide is obtained by dehydrating iron hydroxide prepared by a corrosion process under an inert atmosphere, which can be expressed by the following reaction formula:

[0073] Fe 2+ Fe 3+ -LDH→Fe 3 O 4 +H 2 O

[0074] It should be noted that the prepared integrated iron negative electrode includes a foamed iron skeleton, the crystal structure of iron is still retained inside the skeleton, and the surface is evenly loaded with ferroferric oxide particles. Since the conversion of iron hydroxide to oxide is a high-temperature process, small-sized particles will agglomerate at high temperatures, so after annealing, ferroferric oxide particles with a diameter of 1-2μm are loaded on the skeleton.

[0075] The combination of the three-dimensional structure of the foamed iron and the micron-sized ferroferric oxide active material can effectively inhibit the shedding of the active material caused by volume expansion during the cycle, thereby ensuring the higher specific capacity and rate performance of the iron negative electrode, as well as better cycle stability.

[0076] The iron negative electrode prepared in the present invention can also be used to make a nickel-iron battery. The battery assembled with commercial nickel oxide as the positive electrode and the prepared integrated electrode as the negative electrode has good rate performance and cycle stability.

[0077] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.

[0078] Example 1

[0079] The preparation of the integrated iron negative electrode comprises the following steps:

[0080] S1. Ultrasonicate the purchased foam iron in acetone for 10 minutes, and then ultrasonicate it in ethanol for 10 minutes to remove surface dirt and oil film;

[0081] The pore density of the foam iron is 95ppi, the thickness is 1.5mm, and it is cut into 1cm×1cm;

[0082] S2, soak the cleaned foam iron in chloride salt corrosion solution and stir to corrode for 30 minutes. After the corrosion is completed, wash it with deionized water and dry it in a vacuum drying oven at 60°C for 12 hours;

[0083] The raw materials for preparing the chloride salt etching solution are dilute hydrochloric acid and chloride salt solution, the chloride salt is sodium chloride, the concentration of sodium is 0.1M, the concentration of hydrogen ions is 1M, and the concentration of chloride ions is 1.1M;

[0084] S3. Place the dried foamed iron in a nitrogen-protected tubular furnace at 5°C min -1 The temperature is raised to 800°C at a rate of 100°C and kept at this temperature for two hours. After annealing, the temperature is naturally lowered to obtain an integrated iron negative electrode.

[0085] Example 2

[0086] The preparation process of Example 2 is substantially the same as that of Example 1, except that the etching solution in Example 2 is 1M dilute hydrochloric acid and 0.05M sodium chloride.

[0087] Example 3

[0088] The preparation process of Example 3 is substantially the same as that of Example 1, except that the etching solution in Example 3 is 1M dilute hydrochloric acid and 0.5M sodium chloride.

[0089] Example 4

[0090] The preparation process of Example 4 is substantially the same as that of Example 1, except that the chloride salt in Example 4 is 0.1 M potassium chloride.

[0091] Example 5

[0092] The preparation process of Example 5 is substantially the same as that of Example 4, except that the chloride salt in Example 5 is 0.05 M potassium chloride.

[0093] Example 6

[0094] The preparation process of Example 6 is substantially the same as that of Example 4, except that the chloride salt in Example 6 is 0.5 M potassium chloride.

[0095] Example 7

[0096] The preparation process of Example 7 is substantially the same as that of Example 1, except that the chloride salt in Example 7 is 0.1 M ammonium chloride.

[0097] Example 8

[0098] The preparation process of Example 8 is substantially the same as that of Example 1, except that in Example 8, the temperature was set at 2°C min -1 The temperature is raised to 600°C and kept at this temperature for two hours.

[0099] Example 9

[0100] The preparation process of Example 9 is substantially the same as that of Example 1, except that in Example 9, the temperature was set at 10°C min -1 The temperature is raised to 1000°C and kept at this temperature for two hours.

[0101] Example 10

[0102] The preparation process of Example 10 is substantially the same as that of Example 1, except that the pore density of the foamed iron in Example 10 is 50 ppi.

[0103] Embodiment 11

[0104] The preparation process of Example 11 is substantially the same as that of Example 1, except that the pore density of the foamed iron in Example 11 is 130 ppi.

[0105] Comparative Example 1

[0106] In the prior art, commercial ferroferric oxide active material, conductive carbon black and PVDF binder are mixed in a ratio of 8:1:1 and coated on the foamed iron.

[0107] Comparative Example 2

[0108] Untreated iron foam.

[0109] Comparative Example 3

[0110] The preparation process of Comparative Example 3 is substantially the same as that of Example 1, except that step S2 is not included in Comparative Example 3.

[0111] Comparative Example 4

[0112] The preparation process of Comparative Example 4 is substantially the same as that of Example 1, except that step S3 is not included in Comparative Example 4.

[0113] Comparative Example 5

[0114] The preparation process of Comparative Example 5 is substantially the same as that of Example 1, except that the annealing temperature in Comparative Example 5 is 400°C.

[0115] Comparative Example 6

[0116] The preparation process of Comparative Example 6 is substantially the same as that of Example 1, except that the annealing temperature in Comparative Example 5 is 1200°C.

[0117] Performance Testing

[0118] The above Examples 1-11 and Comparative Examples 1-6 were tested for performance at 4 mA cm -2 and 32mA cm -2 The area specific capacity at 370 °C was calculated, and the capacity retention rate was calculated. The test results are shown in Table 1.

[0119] Table 1 Performance test results

[0120]

[0121]

[0122] Combined with Examples 1-11 and Comparative Examples 1-6 and Table 1 and Figure 1-12 , we can see that:

[0123] (1) The surface of foam iron is relatively smooth ( Fig.12), after chloride salt corrosion, a flake-like micro-nano structure appeared on the surface of the foamed iron ( Figure 1 ), the surface of the iron negative electrode obtained by annealing is transformed into a micro-nano particle structure ( Figure 2 ), the final iron cathode is a composite material of iron and ferroferric oxide ( Figure 3 );

[0124] (2) During the chloride corrosion stage, the concentration and type of chloride will affect the morphology and uniformity of the micro-nanostructures produced during the corrosion process ( Figure 1 , Figure 7-11 ). In the annealing stage, if the annealing temperature is too high (e.g. 1200°C) or too low (e.g. 400°C), the specific capacity of the prepared iron negative electrode will be reduced;

[0125] (3) Under the preferred conditions, the electrode prepared in Example 1 has high electrochemical activity ( Figure 4 )、High Capacity / Rate( Figure 5 ) and long-term circulation stability ( Figure 6 ) characteristics, the other electrodes (Examples 2-11) prepared using the preferred synthesis conditions all have higher performance (Table 1). -2 The specific capacity is 1.33 mAh cm at a current density of -2 Above 32 mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 above.

[0126] The capacity is better than that of the iron negative electrode prepared by the traditional method (Comparative Example 1), and is significantly better than that of the untreated foamed iron electrode (Comparative Example 2), the electrode prepared without the corrosion process (Comparative Example 3) or the electrode prepared without the annealing process (Comparative Example 4), showing the superiority of the chloride salt etching solution provided by the present invention and the iron negative electrode prepared therefrom.

[0127] application

[0128] The iron negative electrode prepared in the above Example 1 and the commercial nickel oxide positive electrode were used to prepare a nickel-iron battery, and the performance of the assembled full battery was tested. Fig.13 and 14 As shown, it can be seen from the CV diagram that there is an obvious redox peak in its charge and discharge process, and from the CP curve diagram of a single battery it can be seen that its discharge voltage is around 1V.

[0129] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A chloride salt corrosive solution, characterized in that: Includes metal cations, hydrogen ions and chloride ions.

2. The chlorine salt corrosive solution according to claim 1, characterized in that: The concentration of the metal cations is 0.1-1M, the concentration of the hydrogen ions is 0.05-2M, and the concentration of the chloride ions is 0.05-3M.

3. The chlorine salt corrosive liquid according to claim 1, characterized in that: The raw materials for preparation are dilute hydrochloric acid and chloride salt solution.

4. The chlorine salt corrosive liquid according to claim 3, characterized in that: The chloride salt is one or more of sodium chloride, potassium chloride, ammonium chloride, calcium chloride and zinc chloride.

5. A method for preparing an iron negative electrode, characterized in that: The following steps are involved: S1. Clean the foam iron with acetone and ethanol to remove dirt and surface oil film; S2, soaking and corroding the cleaned foamed iron in the chloride salt corrosion solution according to any one of claims 1 to 4, then rinsing with deionized water, and finally vacuum drying; S3: annealing the dried foamed iron under the protection of an inert gas, and naturally cooling it to room temperature to obtain an iron negative electrode.

6. The method for preparing the iron negative electrode according to claim 5, characterized in that: The pore density of the foamed iron is 50-130ppi.

7. The method for preparing the iron negative electrode according to claim 5, characterized in that: In step S2, the vacuum drying temperature is 40-80°C, and the vacuum drying time is 6-12 hours.

8. An iron negative electrode, characterized in that It is prepared by the preparation method according to any one of claims 5-7.

9. The iron negative electrode according to claim 8, characterized in that: At 4 mA cm -2 The specific capacity is 1.33 mAh cm at a current density of -2 Above 32 mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 Above, stable cycle more than 300 times.

10. Use of an iron negative electrode prepared by the preparation method according to any one of claims 5 to 7 and the iron negative electrode according to claim 8 or 9 in a nickel-iron battery.